2017
DOI: 10.3389/fmicb.2017.02515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fungal Growth on Olive-Mill Wastewaters Treated at High Temperature and by High-Pressure Homogenization

Abstract: Reuse of olive mill wastewaters (OMWWs) in agriculture represents a significant challenge for health and safety of our planet. Phytotoxic compounds in OMWW generally prohibit use of untreated OMWWs for agricultural irrigation or direct discharge into surface waters. However, pretreated OMWW can have positive effects on chemical and microbiological soil characteristics, to fight against fungal soil-borne pathogens. Low amounts of OMWW following thermal (TT-OMWW) and high-pressure homogenization (HPH-OMWW) pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The results showed that high temperature exhibited more inhibitory effect on the growth and aflatoxin production of these fungi than low temperature ( 36 ). Similarly, Cibelli et al observed that the growth of A. alternata was remarkably inhibited under high-temperature conditions ( 37 ). Moreover, many studies have reported the impact of other processing methods on the fungal community.…”
Section: Discussionmentioning
confidence: 90%
“…The results showed that high temperature exhibited more inhibitory effect on the growth and aflatoxin production of these fungi than low temperature ( 36 ). Similarly, Cibelli et al observed that the growth of A. alternata was remarkably inhibited under high-temperature conditions ( 37 ). Moreover, many studies have reported the impact of other processing methods on the fungal community.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, the application of OMW to fruit infected with gray mold as well as plum tree orchards led to a significant decrease in fungal formation (Saadi et al, 2007;Vagelas et al, 2009). Several types of molds, namely Alternaria, Colletotrichum, Sclerotium, and Rosellinia, species were strongly inhibited by the application of OMW (Cibelli et al, 2017). In contrast, the spreading of OMW to a field of olive trees led to an almost 5-fold increase in arbuscular mycorrhizal fungi, which caused the fungal-bacterial ratio to increase from 0.23 to 1.11 (Mechri et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…B. pumilus (formerly known as Bacillus sp. strain 13M) [ 7 ], C. boidinii (strain 682) [ 8 ] and T. harzianum , strain Var119 [ 9 , 10 ], were used throughout this study. The bacterium was maintained on Tryptone Soya Agar (Oxoid, Basingstoke, UK) at 4 °C and grown in Tryptone Soya broth at 30 °C for 48 h; the yeast was maintained on YPG agar (yeast extract, 10 g/L; peptone, 20 g/L; glucose, 20 g/L) and grown in YPG broth incubated at 25 °C for 72 h, while the fungus was maintained on PDA (potato, 200 g/L; dextrose, 20 g/L; agar 20 g/L) at 4 ± 3 °C, and grown on PDA at 23 ± 2 °C for 15 days in the dark.…”
Section: Methodsmentioning
confidence: 99%